1989
DOI: 10.1099/0022-1317-70-12-3335
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of Host Cell Determinants which Discriminate between Lytic and Persistent Mouse Hepatitis Virus Infection Results in a Fusion-resistant Phenotype

Abstract: SUMMARYThe expression of mouse hepatitis virus (MHV) E2-specific mRNA, the E 2 polypeptide and its associated cell fusing activity was monitored in various cell types inoculated with a recombinant vaccinia virus, designated vMS containing the Ez gene. The results suggest that host cell permissiveness to MHV infection correlates with cellular susceptibility to membrane fusion mediated by the MHV E2 glycoprotein. In addition, we utilized a genetic approach to the analysis of host cell functions involved in deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Interestingly, syncytium formation was also observed in RK 13 cells, which are not susceptible to MHV infection. Previously, it was thought that MHV S protein induced syncytium formation only in mouse cells (Vennema et al, 1990); there is a correlation between permissiveness to MHV and susceptibility to fusion by the S protein (Daya et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, syncytium formation was also observed in RK 13 cells, which are not susceptible to MHV infection. Previously, it was thought that MHV S protein induced syncytium formation only in mouse cells (Vennema et al, 1990); there is a correlation between permissiveness to MHV and susceptibility to fusion by the S protein (Daya et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Sturman and coworkers (Frana et al, 1985) have found that there are significant differences in the susceptibility of murine cell lines to MHV-mediated fusion from without. Similarly Anderson and coworkers (Mizzen et al, 1983;Daya et al, 1989) conclude that host cell permissiveness to MHV infection correlates with cellular susceptibility to membrane fusion. Also, Kooi et al (1991), Cervin & Anderson (1991) and Roos et al (1990) have shown that the susceptibility of cells to MHV-induced fusion can be altered by modification of the membrane lipid composition.…”
Section: Introductionmentioning
confidence: 89%
“…, 1985 ) . The lipid composition of the cell membrane (Daya, et al, 1988;RODS, et aI" 1990), an unknown membrane component (Daya, et al , 1989) may also affect coronav irus-induced cell-cell fusion . The structure of MHV spike glycoprotein has important effects on MHV -induced cell fusion .…”
Section: Introductionmentioning
confidence: 99%